Модель универсального умножителя частоты несущей PSK сигналов - Лимаренко, П. В. (ХНУРЭ, 2009)
This work describes the structure of the frequency multiplier that increases the frequency of PSK-signals carrier.
Keywords: умножитель частоты; PSK сигнал